Parametric study of building codes in other countries on habitability criteria - Manzano, Cedric Jon D.
With the rise in number of high-rise buildings being built in the country, the susceptibility of the Philippines to tropical cyclones, and the trend towards more flexible and slender design, making buildings more vulnerable to responses to wind loads, designing buildings for wind-induced accelerations has become more important than ever. However, NSCP provisions dealing with these are relatively new and are based entirely on ASCE7-10. Thus, conducting a study of available expressions for acceleration in foreign codes may be helpful in better understanding and improving the corresponding provisions in the NSCP. The goal of this research is to perform a parametric analysis of provisions on wind-induced accelerations from five international building codes, determine their sensitivity to input parameters, and make a comparison between them. The study was performed largely by developing simple computer programs and using these to calculate the accelerations based on the codes and performing the parametric analysis. It was found out that NBCC gave the largest along-wind accelerations, NBCC and ASCE7 along-wind accelerations were the most sensitive to height. ASCE7 was the most sensitive to width and wind speed. All codes essentially demonstrated the same sensitivity to depth, natural frequency, and damping. As for across-wind acceleration, AS/NZS gave the highest estimates for all input parameters, except for wind speed. AIJ was the most sensitive to width. AS/NZS was totally insensitive to height and width. ASCE7 gave high values of along-wind acceleration, in fact the second highest among the five codes. Furthermore, the ASCE7 along-wind acceleration is highly sensitive to the wind speed, in comparison to the other input parameters.